Influence of hydrophilicity of cationic polymers on the biophysical properties of polyelectrolyte complexes formed by self-assembly with DNA - Howard, K; Dash, P; Read, M; Ward, K; Tomkins, L; Nazarova, O; Ulbrich, K; Seymour, L (Elsevier, 2000)
To investigate the possibility of producing charge-neutral gene delivery complexes with extended, non-particulate structures, DNA was allowed to self-assemble with a series of hydrophilic cationic polymers containing quaternary charged trimethylammonio ethylmethacrylate (TMAEM, 5, 15, 50, 100 mol%) copolymerised with hydrophilic N-(2-hydroxypropyl)methacrylamide (HPMA, 95, 85, 50, 0 mol%, respectively). Copolymers were all able to bind DNA, assessed using ethidium bromide fluorescence, although copolymers with low TMAEM content did not expel ethidium bromide. Increasing TMAEM content of the copolymers changed the morphology of the complexes from extended (5–15 mol% TMAEM), through partially condensed particles (50 mol%) to discrete nanoparticles (100 mol% TMAEM). Complexes based on copolymers with low TMAEM content (5–50 mol%) showed less resistance to degradation by nucleases and lower surface charge (21.2±5.9–45.1±3.9 mV) than those formed using 100 mol% TMAEM (57.8±8.2 mV). They also showed significantly less association with phagocytic cells in vitro (human leucocytes, uptake decreased by up to 92.3%; murine peritoneal macrophages, uptake decreased by up to 69.6%), although in vivo their hepatic accumulation was only slightly decreased (maximum decrease 27.6%). Finding the appropriate balance of hydrophilicity and stability is key to development of effective vectors for gene delivery.